Multisectoral action to address noncommunicable diseases: lessons from three country case studies - Akselrod, Svetlana; Collins, Téa E.; Berlina, Daria; De Pinho Campos, Katia; Fones, Guy; de Sousa Neves, Diogo; Bashir, Fatima; Allen, Luke N. (Frontiers in Public Health, 2024)
Multisectoral action is a central component of the global response to the rising prevalence of non-communicable diseases (NCDs). This paper unpacks the definition of multisectoral action and provides an overview of the historical context, challenges, and recommendations alongside three country case studies: salt reduction in the UK, tobacco legislation in Nigeria, and regulation of edible oils in Iran. Multisectoral approaches demand multistakeholder engagement that brings the challenge of reconciling competing and conflicting values and priorities. Commercial interests and free trade agreements are the most common obstacles to successful multisectoral strategies that involve the food, alcohol and tobacco industries. Early consultative stakeholder engagement and strong political and bureaucratic leadership are necessary for any multisectoral action programme to be successful.